2022
DOI: 10.1186/s12877-022-02873-3
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative cognitive dysfunction in older surgical patients associated with increased healthcare utilization: a prospective study from an upper-middle-income country

Abstract: Background Perioperative neurocognitive disorder includes postoperative cognitive dysfunction (POCD) and postoperative delirium (POD). Concerning inconclusive consequences of POCD compared with POD, we explored the association between either POCD or POD and functional decline as well as healthcare utilization. Methods Patients aged at least 60 years who underwent a major operation were enrolled. POCD was defined as a decrease in the Montreal Cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 57 publications
(60 reference statements)
0
13
0
1
Order By: Relevance
“…In the present meta-analysis, we found that the LOS of older non-cardiac surgical patients who did not receive intraoperative rSO 2 monitoring was significantly prolonged and was accompanied by an increased incidence of POCD. A recently published prospective study revealed that older surgical patients with POCD are prone to need a prolonged LOS, which suggests the potential consequence of POCD, although clinically subtle, has a noticeable adverse impact on healthcare system expenditure [ 10 ]. Therefore, we should actively apply appropriate strategies, such as intraoperative rSO 2 monitoring, to prevent the occurrence of POCD in a high-risk population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present meta-analysis, we found that the LOS of older non-cardiac surgical patients who did not receive intraoperative rSO 2 monitoring was significantly prolonged and was accompanied by an increased incidence of POCD. A recently published prospective study revealed that older surgical patients with POCD are prone to need a prolonged LOS, which suggests the potential consequence of POCD, although clinically subtle, has a noticeable adverse impact on healthcare system expenditure [ 10 ]. Therefore, we should actively apply appropriate strategies, such as intraoperative rSO 2 monitoring, to prevent the occurrence of POCD in a high-risk population.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that the incidence of POCD in older individuals varies from 16.7 to 89% one week after surgery [6][7][8][9]. It is well established that POCD is associated with a range of negative outcomes, including prolonged hospitalization, changes in mood and personality, reduced quality of life, heavy burden on the family and society, and increased mortality [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies showed that the reductions of neuron number, cognitive related neurotransmitters, and corresponding receptors could cause the decline of cognitive function [ 10 , 11 ]. Other studies showed that surgical trauma was one of the high risk factors for the cognitive dysfunction [ 12 ]. This was because that surgical trauma could cause the release of inflammatory cytokines, which played an important role in the development of cognitive dysfunction [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…38,39 These changes, formerly referred to as postoperative cognitive decline (POCD) and now as postoperative neurocognitive disorder (PNCD), are associated with depression, functional decline, longer hospital stays, long-term care admissions, and billions of dollars in healthcare costs. 40 As the population ages, demand for cardiac surgery is anticipated to rise and the number of patients at risk for PNCD will increase in parallel. Risk factors associated with PNCD have been identified, including age, preoperative conditions including dementia, cognitive impairment, depression, and stroke, and postoperative events including new arrythmias and longer intensive care unit (ICU) stays.…”
Section: Mind the Mind: Understanding Perioperative Neurocognitive Di...mentioning
confidence: 99%